Report of the Phenotype of a Patient with Roberts Syndrome and a Rare ESCO2 Variant - da Costa Almeida, Carla Bastos; Welter, Amanda Thum; Abech, Gabriel Dotta; Brandão, Gabriela Rangel; Flores, José Antônio Monteiro; Schüle, Birgitt; Francke, Uta; Fiegenbaum, Marilu; Zen, Paulo Ricardo Gazzola; Rosa, Rafael Fabiano Machado (Journal of Pediatric Genetics, 2020)
Roberts syndrome is a rare autosomal recessive genetic disease. In this report, we report a Brazilian patient with a rare ESCO2 variant. The patient manifested a broad range of clinical findings including the significant, bilateral shortening of the extremities. He deteriorated and passed away at 20 days of age. High-resolution GTG-banded karyotype showed lack of centromeric constriction in some chromosomes, premature centromere separation in others, and repulsion of the heterochromatin regions. Molecular analysis of the ESCO2 gene revealed a deletion of 4 bp involving exon 4 in homozygosity (NM_00107420.2:c.875_878delACAG), which causes loss of ESCO2 function. We describe the clinical presentation caused by a rare ESCO2 variant.
Keywords: Roberts syndrome; phocomelia; ESCO2 variant